Antimicrobial activity of plantaricin IIA-1A5 on whey growth medium againts Pseudomonas aeroginosa: a scanning electron microscopy (SEM) study - Mutmainna, Andi; Arief, Irma Isnafia; Lestari, Ayu; Hidayat, Muhammad Nur (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
The study aimed to understand antimicrobial properties of plantaricin derived from L. plantarum IIA-1A5 and its inhibitory mechanism against Pseudomonas aeruginosa ATCC 27853 under SEM (scanning electron microscopy) observation. The inhibition of microbial growth was evaluated according to diameter of inhibitory zone. Scanning electron microscopy was then applied to observe the microstructure. The diameter of antimicrobial activity against Pseudomonas aeruginosa ATCC 27853 reached 6.52 mm in whey medium and 8.45 mm in whey+ medium (added with sucrose, tryptone and yeast extract). The experimental result clearly demonstrated the inhibition Pseudomonas aeruginosa ATCC 27853. Observation by SEM suggested that the antimicrobial activity of Pseudomonas aeruginosa ATCC 27853 related destruction of cellular morphology. The cell membrane was destroyed as indicated by the release of nucleic acid and reduction of membrane potential. In short, our experiment provided meaningful evidence on the future use of plantaricin IIA-1A5 as food preservative through disruption of cellular membrane causing leading to cell dying.Keywords:  Plantaricin, Lactobacillus plantarun, Pseudomonas aeruginosa, antimicrobial activity